Prevalence and causes of abnormal liver function in patients with coeliac disease. (21st April 2013) - Casella, Giovanni; Antonelli, Elisabetta; Di Bella, Camillo; Villanacci, Vincenzo; Fanini, Lucia; Baldini, Vittorio; Bassotti, Gabrio
Abstract Background & Aims Coeliac disease patients frequently display mild elevation of liver enzymes and this abnormality usually normalizes after gluten‐free diet. To investigate the cause and prevalence of altered liver function tests in coeliac patients, basally and after 1 year of gluten‐free diet. Patients and methods Data from 245 untreated CD patients (196 women and 49 men, age range 15–80 years) were retrospectively analysed and the liver function tests before and after diet, as well as associated liver pathologies, were assessed. Results Overall, 43/245 (17.5%) patients had elevated values of one or both aminotransferases; the elevation was mild (<5 times the upper reference limit) in 41 (95%) and marked (>10 times the upper reference limit) in the remaining 2 (5%) patients. After 1 year of gluten‐free diet, aminotransferase levels normalized in all but four patients with HCV infection or primary biliary cirrhosis. Conclusions In coeliac patients, hypertransaminaseaemia at diagnosis and the lack of normalization of liver enzymes after 12 months of diet suggest coexisting liver disease. In such instance, further evaluation is recommended to exclude the liver disease. Early recognition and treatment of coeliac disease in patients affected by liver disease are important to improve the liver function and prevent complications.